2014
DOI: 10.1089/end.2014.0360
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Mass Index on Renal Functional Outcomes Following Minimally Invasive Partial Nephrectomy

Abstract: Objective: To assess the impact of body mass index (BMI) on perioperative and renal functional outcomes in patients undergoing minimally invasive partial nephrectomy (MIPN). 19, 45). There were no differences in demographic, perioperative, or pathologic features between BMI groups. While controlling for gender, race, Charlson comorbidity score, tumor size, and ischemia time, obese class 1 (odds ratio [OR] 4.68, p = 0.019), obese class ‡2 (OR 4.27, p = 0.033), and age (OR 1.06, p = 0.014) were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Conversely, in a minimally invasive cohort, Richards and colleagues found obesity to be linked with new onset chronic kidney disease stage 3 and a greater decline in eGFR-findings not supported by our data. 30 Our findings must be understood in the context of the limitations of this retrospective cohort. Although selection for robotic surgery would naturally be a source of bias, it is worth noting that this cohort reflects a wide range of BMIs that closely resembles the American population.…”
Section: Figmentioning
confidence: 86%
“…Conversely, in a minimally invasive cohort, Richards and colleagues found obesity to be linked with new onset chronic kidney disease stage 3 and a greater decline in eGFR-findings not supported by our data. 30 Our findings must be understood in the context of the limitations of this retrospective cohort. Although selection for robotic surgery would naturally be a source of bias, it is worth noting that this cohort reflects a wide range of BMIs that closely resembles the American population.…”
Section: Figmentioning
confidence: 86%
“…Numerous authors have demonstrated this correlation. Richards et al [24] showed that increasing BMI was associated with significant absolute reduction in eGFR at 1 year (0.38 mL/ min/1.73 m 2 reduction in eGFR per 1 kg/m 2 increase in BMI, p = 0.009) after partial nephrectomy. Nozaki et al [25] also showed that the deterioration of renal function Urol Int 2018;101:400-408 DOI: 10.1159/000493763 after donor nephrectomy was negatively correlated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…To preserve nephrons and, in turn, preserve renal function, partial nephrectomy has become the preferred option to radical nephrectomy when removing small renal tumors [ 14 , 17 - 19 ]. Although the more traditional open partial nephrectomy (OPN) is still performed, many have opted for minimally invasive surgical techniques, such as laparoscopic partial nephrectomy (LPN) or robotic partial nephrectomy (RPN), because of their shorter hospital stays and operating times [ 20 ]. With increased precision, dexterity, and 3D capabilities, RPNs are more commonly performed than OPNs or LPNs [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increased likelihood of postoperative complications, both medical and surgical techniques must be assessed to establish the best practice for patients with obesity. Although increased BMI adds another level of difficulty for physicians performing partial nephrectomies, the procedure is considered especially advantageous in this population [ 20 , 23 ]. RPNs have become a more favorable approach in the general population; however, there is still controversy regarding the most efficacious surgical technique in patients with obesity.…”
Section: Introductionmentioning
confidence: 99%